2018
DOI: 10.22271/tpr.2018.v5.i1.002
|View full text |Cite
|
Sign up to set email alerts
|

Simple and efficient method for functional RNA extraction from tropical medicinal plants rich in secondary metabolites

Abstract: Isolation of high-quality functional RNA is prerequisite to facilitate any study related to gene expression and also for downstream applications such as reverse transcription-polymerase chain reaction (RT-PCR), suppression subtractive hybridization (SSH) library construction, differential display (DD), real-time PCR and northern hybridization of medicinal plants. Tropical medicinal plants are rich in polysaccharides, polyphenolics and secondary metabolites that are reported to interfere with the successful RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 10 publications
1
10
1
4
Order By: Relevance
“…Tissue form, i.e. whole or crushed, will most likely also have an impact during transport or preservation (Johnson et al, 2012;George, 2018). We observed that (both FD and non-FD) crushed samples resulted in higher RNA yields in comparison to whole bean preservation.…”
Section: The Importance Of Preservation and Transportationmentioning
confidence: 75%
See 1 more Smart Citation
“…Tissue form, i.e. whole or crushed, will most likely also have an impact during transport or preservation (Johnson et al, 2012;George, 2018). We observed that (both FD and non-FD) crushed samples resulted in higher RNA yields in comparison to whole bean preservation.…”
Section: The Importance Of Preservation and Transportationmentioning
confidence: 75%
“…Also differences in RNA purities were observed between the Sangha and the MacKenzie buffer. PVP, combined with NaCl and CTAB (Sangha) or guanidium thiocyanate (MacKenzie), prevents polyphenol oxidization and aids in contaminant-removal from nucleic acid extracts ( Mornkham et al., 2013 ; George, 2018 ). Although PVP is present in both the Sangha and the MacKenzie buffer, the A 260/230 ratios were lower for the Sangha buffer, indicating polysaccharide and polyphenol contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Los compuestos fenólicos presentes en las muestras de tejido se oxidan rápidamente para formar quinonas. Estas quinonas pueden unirse fácilmente con ácidos nucleicos y actuar como una barrera para el aislamiento de ARN de buena calidad (George, 2018).…”
Section: Resultados Y Discusiónunclassified
“…The extraction of total RNA is one of commonly used techniques in molecular biology experiment [6]. RNA is prerequisite to facilitate any study related to gene expression and also for downstream applications such as RT-PCR, library construction, real-time PCR and northern hybridization [7]. Therefore, undegraded and intact RNA free of DNA, protein and other impurities are particularly important.…”
Section: Introductionmentioning
confidence: 99%